2016
DOI: 10.1038/ejcn.2016.139
|View full text |Cite
|
Sign up to set email alerts
|

The gluten-free basic food basket: a problem of availability, cost and nutritional composition

Abstract: The basic food basket (BFB), formed by the more economical products available, is used by less-affluent countries to establish the minimum daily food consumption to satisfy nutritional requirements in less-privileged individuals. There is no information about groups that depend on the BFB and in addition follow gluten-free diet (GF/BFB). We measured availability, cost, main ingredients and nutritional composition of GF/BFB. Data were collected in the area that was first in the social priority list in the capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 6 publications
5
38
0
4
Order By: Relevance
“…No obstante, revisiones actuales no pueden establecer si la DSG mejora o no la CVRS debido a que existen múltiples factores que hacen a esta dieta difícil de llevarse: costos, accesibilidad, palatabilidad, etcétera 24,26 . Un estudio realizado en 2016 en Chile demostró que los alimentos sin gluten están menos disponibles, son tres veces más costosos y contienen menos proteínas y vitaminas 27 . Se desconoce esta situación y su implicancia en la CVRS en Paraguay, donde los alimentos derivados del maíz y mandioca, de fácil acceso, forman parte del acervo cultural.…”
Section: Discussionunclassified
“…No obstante, revisiones actuales no pueden establecer si la DSG mejora o no la CVRS debido a que existen múltiples factores que hacen a esta dieta difícil de llevarse: costos, accesibilidad, palatabilidad, etcétera 24,26 . Un estudio realizado en 2016 en Chile demostró que los alimentos sin gluten están menos disponibles, son tres veces más costosos y contienen menos proteínas y vitaminas 27 . Se desconoce esta situación y su implicancia en la CVRS en Paraguay, donde los alimentos derivados del maíz y mandioca, de fácil acceso, forman parte del acervo cultural.…”
Section: Discussionunclassified
“…En un segundo estudio evaluamos la Canasta Básica Familiar Sin Gluten (CBF/SG) (35). El concepto CBF es usado en nuestro país para establecer el consumo mínimo de alimentos que deben mantener cada integrante de una familia que en promedio está formada por 4 miembros, para cubrir los requerimientos nutricionales.…”
Section: El Mercado De Alimentos Sin Gluten En Chileunclassified
“…Coinciding with them, Estevez et al [35] found, when analysing the basic basket of glutenfree products available in Chile, that regular wheat-based foods like biscuits and noodles contain 50% more ibre than their gluten-free equivalents, which also contain 24% less protein, on average. In addition, dairy products, like gluten-free cheese and yogurts, can have up to 52.4% more sodium than the regular ones.…”
Section: Nutrition Quality Of the Gluten-free Dietmentioning
confidence: 99%
“…Due to the technological diiculty for obtaining high-quality gluten-free products and to their lower market demand than their conventional food counterparts, they can be up to 300% more expensive [35]. Therefore, an option for people with gluten-related disorders is the home preparation of foods from unprocessed sources to devise a balanced gluten-free diet.…”
Section: Nutrition Quality Of the Gluten-free Dietmentioning
confidence: 99%
See 1 more Smart Citation